Susceptibilidad a deslizamientos a escala 1:5000, de la Zona Central de la Parroquia Selva Alegre, Cantón Saraguro, Provincia de Loja. - Castillo Prado, Cristhian Nicanor (2023)
The present research work "Susceptibility to Landslides at 1:5000 scale, of the Central Zone of the Selva Alegre Parish, Saraguro Canton, Loja Province" has an area of 1505.46 hectares. In the first place, the information was collected in the office, to then proceed in the field to the generation of the topography, in which slopes, water network, road network, infrastructure and towns of the study area were considered, being the basis for the realization of the variables considered for the susceptibility map. For the cartographic preparation, use was made of the quantitative method Hierarchical Analysis Process (Analytical Hierarchy Process, AHP), proposed by Thomas Saaty in 1980, with which the assessment, weighting and normalization of each of the variables carried out was achieved. Within the elaboration of the susceptibility map, the ArcGIS 10.5 program was used, in which the maps for each variable were made, in turn making use of the ArcMap tools, gave way to the analysis, correlation and interpretation of the data obtained in field, and allowed the assignment of weights to the variables considered in the area (Slopes, Geomorphology, Land Use and Geology), thus sectorizing the study area, for the final categorization of the susceptibility map. Finally, to demonstrate the results of this project, we proceeded to zone the areas susceptible to landslides represented in a final susceptibility map developed under Datum WGS 84 - Zone 17 South, with which it is possible to qualify each of these areas, in the face of possible phenomena geological. Key Words: Susceptibility, Landslides, Saaty, Geology, Geomorphology, land use